2010
DOI: 10.1111/j.1756-2589.2010.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

From Partnership to Parenthood: A Review of Marital Change Across the Transition to Parenthood

Abstract: The transition to parenthood is generally seen as one of the most challenging events in the early stages of marriage. But is it really that detrimental for marriage and do all couples go through the same changes? This article provides a state‐of‐the‐art review of research on marital change across the transition to parenthood. I first address to what extent the transition to parenthood affects the partner relationship. I then consider factors that explain why some couples fare better or worse than others across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
197
2
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(221 citation statements)
references
References 92 publications
10
197
2
12
Order By: Relevance
“…The transition to parenthood is an opportune time for couplesbased interventions (Glade et al, 2005) as marital satisfaction often declines following the birth of a child as the focus of attention shifts from the self and the partner to the needs of the infant (Kluwer, 2010;Shapiro et al, 2000). The birth of a child leads to increased household labor (Kluwer, 2010), increased conflict (Shapiro et al, 2000), and less opportunities for shared leisure activities and intimacy (Shapiro and Gottman, 2005).…”
Section: The Prevention Of Perinatal Depression and Anxietymentioning
confidence: 98%
See 1 more Smart Citation
“…The transition to parenthood is an opportune time for couplesbased interventions (Glade et al, 2005) as marital satisfaction often declines following the birth of a child as the focus of attention shifts from the self and the partner to the needs of the infant (Kluwer, 2010;Shapiro et al, 2000). The birth of a child leads to increased household labor (Kluwer, 2010), increased conflict (Shapiro et al, 2000), and less opportunities for shared leisure activities and intimacy (Shapiro and Gottman, 2005).…”
Section: The Prevention Of Perinatal Depression and Anxietymentioning
confidence: 98%
“…The birth of a child leads to increased household labor (Kluwer, 2010), increased conflict (Shapiro et al, 2000), and less opportunities for shared leisure activities and intimacy (Shapiro and Gottman, 2005). The physical demands of parenting, such as breastfeeding and sleep disturbance, place additional pressure on couples (Petch and Halford, 2008).…”
Section: The Prevention Of Perinatal Depression and Anxietymentioning
confidence: 99%
“…As indicated by Boyce et al (2007) it is unclear whether the elevated depressive symptoms is a consequence of a poor intimate relationship that is further strained by the pregnancy or whether the distress of finding out that their partner is pregnant leads to a decline in the satisfaction with the relationship. Given that some studies suggest that at least half of couples report a decline in marital satisfaction following childbirth (Kluwer, 2010), it may be particularly important to include adaptive couple strategies (e.g., division of labor, couple communication, co-parenting, problem solving) as part of prenatal preparation to prevent relationship quality from declining following childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…While the transition to parenthood is often viewed as a positive and joyful life event, it can be perceived as a stressful experience, negatively affecting psychological and marital resources for each partner in the couple (Kluwer, 2010;Whisman, Davila, & Goodman, 2011). The few studies conducted with fathers have reported that paternal psychological distress is related to destructive health behaviors (i.e., greater use of alcohol and cigarettes) in fathers, maternal postpartum depression, and the quality and level of paternal involvement with the child (Lamb, 2004;Ramchandani et al, 2008;Sethna, Murray, Netsi, Psychogiou, & Ramchandani, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Parenthood restructures the family unit, because caring for an infant shifts the couple's priorities. Both partners must adjust to having less time, energy, and cognitive capacity to remain responsive to each other's needs (Crnic & Low, 2002;Kluwer, 2010;Twenge, Campbell, & Foster, 2003). Typical stressors include (a) role changes when many women become the primary caregiver and many men carry more financial burden; (b) decreases in perceived freedom because parents responsibly focus on the infant; (c) decreases in sexual intimacy; (d) financial stress and medical conditions that impact the mother's health; and (e) lack of social support (Giurgescu et al, 2015;Perren, von Wyl, Bürgin, Simoni, & von Klitzing, 2005;Twenge et al, 2003).…”
Section: The Transition To Parenthoodmentioning
confidence: 99%